The sports event’s quality towards attendance of tourists at sports event hosted at Northern Zone of Malaysia / Khor Poy Hua, Lim Khong Chiu and Radzliyana Radzuwan - Khor, Poy Hua; Lim, Khong Chiu; Radzuwan, Radzliyana (Universiti Teknologi MARA, Negeri Sembilan, 2019)
Sports tourism is an essential part of world tourism and is trendy in Malaysia. Malaysia recorded about 25.83million tourist arrivals in 2018. Efficient delivery of hospitality services to the sports tourists will contribute to the multi-billion-dollar sports tourism business.In a competitive sports tourism market, offering sporting event requires being deeply acknowledged with the reasons that attracts tourists’ choice of specific sporting event and the degree of satisfaction that these sports tourists perceived from the service provided. As so,thispresent study discusses on the sports event’s quality towards attendance of tourists at sports event hosted at northern zone of Malaysia. The objectives of this study are answered based on survey research conducted among 351 sports tourists at the sports event organized at northern zone of Malaysia. The study reveals that the intangible aspect of sports event’s quality highly affects tourists’ attendance at sports event hosted in Northern Zone of Malaysia, compared to the tangible aspect. Growing economy plays an important role in ensuring the quality of sports event. Findings reveal dissimilarities on perception of quality towards sports event between the gender groups, with the male tourists displaying higher sensitivity. Further study on sports events hosted in other region of Malaysia could contribute to development of quality sports events in promoting Malaysia as an international sports tourism destination.